Plant regeneration in callus culture of brazilian wheat genotypes - Milach, Sandra C. K; Federizzi, Luiz Carlos; Carvalho, Fernando Irajá Félix de; Dornelles, Ana Lucia Cunha; Lange, Claudia (Pesquisa Agropecuaria Brasileira, 1991)
Sixteen wheat genotypes were evaluated for in vitro plant regeneration. Immature wheat embryos were inoculated on MS medium with 5 mg and 2 mg/1 2,4D to callus initiation. The rest of culture was done on MS medium with 0,5 mg/1, 0,2 mg/1 and without 2,4D in the media. The metodology used was suitable to regenerate plants of different Brazilian wheat genotypes. Variability among genotypes was observed to plant regeneration. Regenerative capacity changed, however, with different levels of 2,4D. The offspring of Nobre and Maringá genotypes from in vitro regenerated plants was evaluated on field to plant height, heading date and spikelet number and seed number per spike. Somaclonal variation was observed in both genotypes to all evaluated traits.